A model for the evaluation of fatality likelihood associated with falls from heights. (March 2020) - Spearpoint, Michael; Hopkin, Charlie
Abstract: The likelihood of a fatality associated with of a fall from height depends on factors such as the distance fallen, the age of the casualty and the impact surface. In this work a review of the literature and an examination of the energy involved in a fall has been used to formulate an empirical approach to predict the likelihood of a fatal outcome using these three features. The predictive capability of the approach is assessed against data presented in the literature with reasonable success. Application of the method for an adult falling onto a hard surface predicts a 50% fatality likelihood at 15 m and a 90% fatality likelihood at 23.8 m. This paper provides a convenient method to predict the likelihood of fatality associated with falls from heights that can account for the height of the fall, the age of the casualty, the impact surface and the injuries sustained. Within the context of fire safety design, the model provides a pathway to assessing the likelihood of a fatality occurring should people need to escape from a building by means of an external window or similar.